THE INFLUENCE OF ONLINE CUSTOMER REVIEWS AND ONLINE CUSTOMER RATINGS ON INTEREST IN PURCHASING PRODUCTS ON SHOPEE WITH TRUST AS A MEDIATION VARIABLE - Dinanti, Novita Adelia; Irmawati, Irmawati (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study was to analyze the effect of online customer reviews and online customer ratings on product purchase interest at Shopee with trust as a mediating variable. Respondents in this study were 130 respondents who were conducted through an online survey with google form. The sampling technique used purposive sampling technique. Validity and reliability tests using smartPLS analysis on the outer model. Hypothesis testing using smartPLS inner model. The results of the analysis show that online customer reviews do not have a significant effect on purchase interest while online customer ratings have a significant effect on purchase interest. Online customer reviews and online customer ratings have a significant influence on trust. Trust has a significant effect on purchase interest. Trust partially mediates the relationship between online customer reviews and online customer ratings on purchase interest.